Dolphin Morbillivirus, a major threat for Mediterranean fin whales (Balaenoptera physalus) - Mazzariol S; Centelleghe C; Beffagna G; Povinelli M; Terracciano G; Cocumelli C; Pintore A; Denurra D; Casalone C; Pautasso A; DI FRANCESCO, Cristina Esmeralda; Di Guardo G. (2016)
Between 2011 and 2013, Dolphin Morbillivirus (DMV) was molecularly identified in four Mediterranean fin whales (Balaenoptera physalus), with the responsible strain showing a high nucleoprotein, phosphoprotein and hemoagglutinin gene sequence homology with the virus causing the 2006-‘07 Mediterranean epidemic. In conclusion, DMV represents a serious threat for fin whales.